The effectiveness of supportive work environment toward employee retention: Millenial generations at Putra Specialist Hospital, Melaka / Farah Nadia Murad - Murad, Farah Nadia (Faculty of Business and Management, 2018)
Employee is an asset of a human capital which gives contribution and outcome to the organization. Retention is the important to the organization because if the organization does not have the power to hold the retention strategies, they are spending too much on the cost of recruiting new employees and it would affect the financial stability of the organization. Employee retention are important for the organization in order to make sure that they are not losing crucial human capital in the organization. For that reason, knowing the whether supportive work environment that can enhance the employee retention is important for organization as to increase the employee retention. Therefore, this research was conducted to know the effectiveness of supportive work environment towards employee retention at Putra Specialist Hospital, Melaka. The objective of this research is to find out the relationship between supportive work environment which are perceived climate, supervisory relationship and perceived organizational support with employee retention. Besides that, the objective is to identify the most factors that influence employee retention. This research was using method non-probability snowball sampling. Questionnaire collected from 104 of respondents at Putra Specialist Hospital, Melaka were analyzes using SPSS. Regression result shows that two (2) factors which are perceived climate and perceived organizational support are significant and influences employee retention. However, one factor (1) which is supervisory relationship found insignificant.